The Impact of Roads on Poverty Reduction : A Case Study of Cameroon - Gachassin, Marie; Najman, Boris; Raballand, Gael (World Bank, Washington, DC, 2014)
Many investments in infrastructure are built on the belief that they will ineluctably lead to poverty reduction and income generation. This has entailed massive aid-financed projects in roads in developing countries. However, the lack of robust evaluations and a comprehensive theoretical framework could raise questions about current strategies in Sub-Saharan Africa. Using the second Cameroonian national household survey (Enquete Camerounaise Aupres des Menages II, 2001) and the Cameroon case study, this paper demonstrates that investing uniformly in tarred roads in Africa is likely to have a much lower impact on poverty than expected. Isolation from a tarred road is found to have no direct impact on consumption expenditures in Cameroon. The only impact is an indirect one in the access to labor activities. This paper reasserts the fact that access to roads is only one factor contributing to poverty reduction (and not necessarily the most important in many cases). Considering that increase in non-farming activities is the main driver for poverty reduction in rural Africa, the results contribute to the idea that emphasis on road investments should be given to locations where non-farming activities could be developed, which does mean that the last mile in rural areas probably should not be a road.